Twitter matters for metaverse stocks amid economic uncertainty - Ahmet Faruk Aysan (11902115) (2023)
The study examines the relationship between economic uncertainty, as measured by the Twitter-based economic uncertainty index (TEU), and Metaverse stocks across different time-frequency domains. By employing Wavelet Local Multiple Correlation analysis, we identify a substantial and statistically significant correlation between TEU and the Metaverse stock market across all time horizons examined. The positive correlation is confirmed when two alternative measures of economic uncertainty: crude oil and gold volatility, are included. The results highlight the importance of considering real-world economic uncertainty in decision-making processes involving virtual reality environments. Other Information Published in: Finance Research Letters License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.frl.2023.104116